Hepatitis-associated Aplastic Anaemia in Children - Böske, Anne-Kathrin; Sander, Annette; Sykora, Karl-Walter; Baumann, Ulrich; Pfister, Eva-Doreen (Klinische Pädiatrie, 2020)
Background Children with idiopathic acute liver failure (IALF) are at a high risk of developing life-threatening bone marrow failure (BMF). The aim of the study was to describe the development, therapy and prognosis of this hepatitis-associated aplastic anaemia (HAAA) in comparison to isolated acquired aplastic anaemia.Results We retrospectively found 18 patients (9 female) of HAAA between 1984 and 2017 with an age of 1.4–16.4 years. Fifteen of them fulfilled the SAA criteria, 3 had a bone marrow hypoplasia. Eleven of these children received liver transplantation (LTx) (these were 11 of 42 (26%) children receiving LTx for IALF), 6 patients recovered without LTx. The first signs of BMF, thrombocytopaenia and leucocytopaenia, occurred before LTx in all cases. During the follow-up period 8 patients reached haematological remission, 6 received haematopoietic stem cell transplantation (HSCT). Seven children died in a median of 304 days after the first symptoms mostly because of bleedings and infections. To date, extensive investigations failed to detect a genetically, viral or immunological aetiology. No AA was diagnosed in the 41 patients receiving liver transplants during the same period for ALF of known aetiology. As a comparison group, we collected the data of patients with isolated SAA. 73% achieved a remission after Immunosuppressive therapy (IST) without HSCT, and none of them died during the follow-up period.Conclusion Blood counts should be examined early and regularly (0–22 days after onset) in patients with IALF. Aggressive treatment with LTx, IST and HSCT appears to improve the prognosis.
Keywords: acute liver failure; seronegative hepatitis; liver transplantation; aplastic anaemia; bone marrow failure; bone marrow transplantation/haematopoietic stem cell transplantation